Literature Review, Critical Thinking Skills in Primary School Students - Andi Dewi Riang Tati (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This research aims to determine critical thinking skills at the elementary school level, especially in the implementation of the "Kurikulum Merdeka” based on a literature review. This research is a literature review which is part of qualitative research. The collection of sources was obtained from literature, both books and articles and other sources that support this research. Based on the findings from the literature review, students' critical thinking abilities at elementary school level are determined by several factors, such as, learning motivation, intellectual development, learning independence, models, strategies and learning media used by teachers.